Post-Disaster Restoration and Revitalization Concept for the Souraja Traditional House Area, Palu City - Irdinal Arief; Khairin rahmat; Rahmat Aris Pratomo (Jurnal Arsitektur, 2026)
The earthquake, tsunami, and liquefaction that struck Palu City, Indonesia, on 28 September 2018 damaged cultural heritage assets, including the Souraja Traditional House in Lere Village. This study aims to formulate an integrated post-disaster restoration and revitalization concept that preserves architectural authenticity and cultural significance. A qualitative approach employed field observations, architectural measurements, semi-structured interviews with traditional leaders, local communities, stakeholders, and document and literature reviews. Spatial, descriptive, and normative analyses evaluated existing conditions and formulated restoration and revitalization strategies. The findings identified three restoration priorities: strengthening the lower structural system while maintaining the original pedestal foundation concept, repairing deteriorated timber flooring, and restoring the roof using materials compatible with the original architectural character. The proposed revitalization strategy improves accessibility, green open spaces, parking management, pedestrian circulation, and community-based commercial activities to strengthen heritage tourism. The integrated framework provides practical guidance for post-disaster management of cultural heritage sites in Indonesia..